Co-localization and confinement of ecto-nucleotidases modulate extracellular adenosine nucleotide distributions - Rahmaninejad, Hadi; Pace, Tom; Bhatt, Shashank; Sun, Bin; Kekenes-Huskey, Peter (PLOS Computational Biology, 2020)
Author summary Nucleotides are important signaling molecules. Their relative concentrations on the extracellular side of plasma membranes are tightly-controlled by nucleotidases. CD39 and CD73 are two such nucleotidases that sequentially convert the nucleotide adenosine tri-phosphate into adenosine, yet little is known about the efficiency of these enzymes in synapse-like junctions formed between neighboring cells. We therefore performed computer simulations of CD39- and CD73-catalyzed reactions in synapse-like junction geometries to understand how these enzymes work between neighboring cells relative to in vitro (cell-free) conditions. Our simulations reveal how properties like cell membrane charge and CD39/CD73 co-expression determine the relative balance of ATP and Ado along the cell exterior. Our approach and quantification of CD39 and CD73 activity at the cell membrane is expected to yield important insights into diverse nucleotidase-dependent phenomena, including tumor growth and regulation of immune responses.